2010
DOI: 10.1016/j.jacc.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Iodine-123 Meta-Iodobenzylguanidine Imaging and Cardiac Events in Heart Failure

Abstract: ADMIRE-HF provides prospective validation of the independent prognostic value of (123)I-mIBG scintigraphy in assessment of patients with HF. (Meta-Iodobenzylguanidine Scintigraphy Imaging in Patients With Heart Failure and Control Subjects Without Cardiovascular Disease, NCT00126425; Meta-Iodobenzylguanidine [123I-mIBG] Scintigraphy Imaging in Patients With Heart Failure and Control Subjects Without Cardiovascular Disease, NCT00126438).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
244
4
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 772 publications
(267 citation statements)
references
References 24 publications
10
244
4
9
Order By: Relevance
“…In light of the results from SHIFT and these other analyses, the paradigm of aiming for the highest tolerated dose of beta blocker may need to be shifted to aiming for a lower heart rate. This concept clearly warrants further prospective study.None of the studies mentioned previously assessed the prognostic value of cardiac 123 I‐ m IBG uptake, a measurement that has repeatedly been shown to be predictive 18, 25, 26, 27, 28, 29. The present study demonstrated the potential value of cardiac 123 I‐ m IBG uptake as a supplementary measure of sympathetic nervous system activity.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…In light of the results from SHIFT and these other analyses, the paradigm of aiming for the highest tolerated dose of beta blocker may need to be shifted to aiming for a lower heart rate. This concept clearly warrants further prospective study.None of the studies mentioned previously assessed the prognostic value of cardiac 123 I‐ m IBG uptake, a measurement that has repeatedly been shown to be predictive 18, 25, 26, 27, 28, 29. The present study demonstrated the potential value of cardiac 123 I‐ m IBG uptake as a supplementary measure of sympathetic nervous system activity.…”
Section: Discussionmentioning
confidence: 52%
“…In previous ADMIRE‐HF multivariate analyses for predictors of death, use of HF medications (angiotensin converting enzyme inhibitors/angiotensin receptor blockers, beta blockers, and aldosterone receptor antagonists) did not affect the final models 18, 29. To examine for interactions between HF medications and the four variables used in the present study, mortality analyses were performed first without and then with inclusion of binary variables of use of angiotensin converting enzyme inhibitors/angiotensin receptor blockers, aldosterone receptor antagonists, and diuretics.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations